Incomplete abortion following medical method of abortion: study at a tertiary care teaching hospital at Bihar - ., Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Medical method of abortion (MMA) is a safe and effective method of abortion. Combination of mifepristone and misoprostol is most widely used. However, this is being randomly used by women without proper prescription which can lead to life threatening complications. Methods: This is an observational study done at Patna Medical College and Hospital, Patna, a tertiary care teaching hospital in Bihar, in a period of one year from March 2019 to February 2020. This is an attempt to study incomplete abortion after medical method of abortion and to observe the method of taking it among patients, with prescriptions or without it. Hundred women with incomplete abortion following MMA in 1st trimester of pregnancy were included. Patients’ age, parity, gestational age, locality, complaints, complications and treatment were noted. An information regarding method of administration and prescription noted. Results: 96% women used combined mifepristone plus misoprostol drug. Only 12% took the medicine on prescription of MBBS doctor, rest were all either self-administered or advised by quacks. Blood transfusion was required in 60% patients. Conclusions: Medical method of abortion is safe and effective but complications can occur if not used in accordance with guidelines. Women should be taught about and motivated for contraception. Adequate training to health care providers about comprehensive abortion care should be given.